Attractiveness of initial vocational education and training : identifying what matters - (:unkn) unknown (Publications Office of the European Union, 2014)
"This research paper addresses the wish to improve the evidence base for policy decisions and actions at national and European Union (EU) level to increase the attractiveness of initial vocational education and training (IVET). Previous studies on how attractive people find VET as learning path have focused on the influence of specific characteristics of the initial VET system. These include the provision of guidance and counselling, the chances to move on to higher education, the qualifications system, or quality assurance for the training provided. But even though an IVET system produces good outcomes it is not necessarily seen as an attractive learning option. This study reveals other wider issues that might be crucial to understanding what makes initial VET and attractive option to potential students. It shows that the composition and respective strengths of the labour market, expenditure on vocational education, as well as wider factors such as views of family members, perceptions about the quality of VET and the wider educational context all play a role. The study concludes with several insights on how to influence perceptions of VET." The study includes total of 10 case studies of policy initiatives from six countries (Germany, Finland, Ireland, Czech Republic, Denmark, Spain) to see what works, and why, in different national contexts. (Editor, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; T 1.5 International vergleichende Berufsbildungsforschung; Berufsausbildung; Attraktivität; Fallstudie; Europa; Bundesrepublik Deutschland; Finnland; Irland; Tschechische Republik; Dänemark; Spanien